1999
DOI: 10.1364/josaa.16.002643
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction tomography using power extinction measurements

Abstract: We propose a new method for determining structures of semitransparent media from measurements of the extinguished power in scattering experiments. The method circumvents the problem of measuring the phase of the scattered field. We illustrate how this technique may be used to reconstruct both deterministic and random scatterers. © 1999 Optical Society of America [S0740-3232(99)00211-2] OCIS codes: 290.3200, 110.6960. Let us consider the power extinguished from a coherent beam consisting of two monochromatic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…In Refs. [8,9] the incident field was taken to consist of two plane waves and consequently the extinguished power was related to a Fourier transform [8] or to a Fourier-Laplace transform [9] of the object. The present result shows that the extinguished power is a meaningful measure of object structure for certain forms of the incident field.…”
Section: ͑53͒mentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [8,9] the incident field was taken to consist of two plane waves and consequently the extinguished power was related to a Fourier transform [8] or to a Fourier-Laplace transform [9] of the object. The present result shows that the extinguished power is a meaningful measure of object structure for certain forms of the incident field.…”
Section: ͑53͒mentioning
confidence: 99%
“…It has been shown that the generalized optical theorem may be used to relate extinguished power to the structure of the scattering object and even to reconstruct the spatial structure of the scatterer from the data obtained from power extinction experiments [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Whether involving holographic or non-holographic methods [10][11][12][13][14][15][16] , QPI presents new opportunities for studying cells and tissues non-invasively, quantitatively and without the need for staining or tagging [17][18][19][20][21][22][23] . Projection tomography using laser QPI has made use of ideas from X-ray imaging and enabled three-dimensional imaging of transparent structures [24][25][26] . More recently, this method has been applied to live cells [27][28][29][30] .…”
mentioning
confidence: 99%
“…Thus, quantitative phase imaging (QPI) has recently become an active field of study and various experimental approaches have been proposed [3][4][5][6][7][8][9][10][11]. Advances in phase-sensitive measurements enabled optical tomography of transparent structures, following reconstruction algorithms borrowed from X-ray computed imaging, in which scattering and diffraction effects are assumed to be negligible [12][13][14][15][16]. Further, QPI-based projection tomography has been applied to live cells [17][18][19].…”
Section: Introductionmentioning
confidence: 99%